High Load Jacking Frames for Pin and Hanger Replacement at the Robert Moses Causeway. Issue 3 (March 2021) - Han, Liwei; Ye, Qi; Wei, Dan
An innovative design of jacking frames was developed for pin and hanger replacement in Robert Moses Causeway (RMC) bridge in Suffolk County, New York. The robust and efficient design of the jacking frames results in a system with improved safety, performance, constructability, and economy. A fully integrated approach for design, fabrication, and construction was employed for higher quality and efficiency. A detailed and precise 3D model was created and directly used for finite element (FE) modeling, producing contract and shop drawings, and designing of temporary work platforms. This paper provides an overview of the integrated design approach and system design, and documents the computational study for this system (global analysis, stress analysis, and large-displacement stability analysis). There are many aging steel bridges in the U.S. and abroad that have similar pin and hanger systems, and jacking frames will be needed to replace those pins and hangers when they exhaust their useful service life. The concepts and details of the jacking frames can easily be emulated by engineers for developing similar safe and robust systems for suspended truss spans and other applicable bridge structures.